Recipes of success : the case of pulp and paper industry 1989-2015 - Nguyen, Khoa (2017)
Explaining the variation in competitive positioning actions across firms in the face of environmental change has long inspired debates in the field of strategic management. Despite the importance of these questions, little effort has been done to examine the complex interdependencies among industry, organizational attributes, and strategic actions that potentially underlie the organizational performance in one model without controlling one or more of the three factors. Most of the studies on competitive dynamics primarily have focused on independently exploring the effects of organizational characteristics or the industry structure on competitive actions and reactions, which, in turn, impact performance. Such causality is also difficult to model and hence has been has largely ignored previously, probably due to the limitations in the correlation-related and variance decomposition approach.